Factors Affecting Unmet Healthcare Needs of Working Married Immigrant Women in South Korea. - Jinseon Yi; Insook Lee (Journal of Korean Academy of Community Health Nursing / Jiyeog Sahoe Ganho Hakoeji, 2018)
Purpose: This study was conducted to identify the factors affecting on unmet healthcare needs of married immigrant women, especially who are working in South Korea. Methods: It is designed as a cross-sectional descriptive study. We analyzed data from 8,142 working married immigrant women to the 'National Survey of Multicultural Families 2015.' Based on Andersen's health behavior model, logistic regression was conducted to determine the predictors of unmet healthcare need. Results: The prevalence of unmet healthcare needs among the subjects was 11.6%. In multivariate analysis, significant predictors of unmet needs included existence of preschooler, country of origin, period of residence in predisposing factors, monthly household income, helpful social relationship, social discrimination, Korean proficiency, working hour per week in enabling factors, and self-rated health, experience of grief or desperation in need factors. Conclusion: The association between labor-related factors and unmet healthcare needs of marriage immigrant women currently working was found from nationally representative sample. Support policies for immigrant women working more than legally defined hours and having preschooler should be supplemented to reduce unmet healthcare needs. In addition, eradicating discrimination in workplace, enlarging social relationship, and developing culturally competent nursing services tailored to health problems caused by labor are needed.